(untitled) (Research, Society and Development, 2026)
This study aims to discuss the relevance of dental prenatal care a preventive strategy to reduce adverse pregnancy outcomes, as well as the primary systemic changes characteristic of the gestational period, based on a systematic literature review. The search was conducted across major scientific databases, selecting studies published over the last two decades that addressed the relationship between oral health and pregnancy. Analysis revealed that oral infections, particularly periodontal disease, are directly associated with complications such as gestational diabetes, cardiovascular disease, and preterm birth, through systemic inflammatory processes mediated by cytokines and other inflammatory mediators. It was observed that integrating dental care into the multidisciplinary team contributes to the control of risk factors, the promotion of healthy habits, and improvements in maternal-child health by reducing the transmission of pathogenic microorganisms to the newborn. Physiological changes during pregnancy require individualized dental management, with specific attention to drug safety, patient positioning, and effective pain control strategies. In conclusion, the incorporation of oral health into prenatal care is essential for improving maternal and neonatal outcomes, with positive repercussions for the pregnant woman’s physical and emotional well-being.